Repair and regeneration of peripheral nerve injuries that ablate branch points - JuliAnne E Allgood; George D Bittner; Jared S Bushman (Neural Regeneration Research, 2023)
The peripheral nervous system has an extensive branching organization, and peripheral nerve injuries that ablate branch points present a complex challenge for clinical repair. Ablations of linear segments of the PNS have been extensively studied and routinely treated with autografts, acellular nerve allografts, conduits, wraps, and nerve transfers. In contrast, segmental-loss peripheral nerve injuries, in which one or more branch points are ablated so that there are three or more nerve endings, present additional complications that have not been rigorously studied or documented. This review discusses: (1) the branched anatomy of the peripheral nervous system, (2) case reports describing how peripheral nerve injuries with branched ablations have been surgically managed, (3) factors known to influence regeneration through branched nerve structures, (4) techniques and models of branched peripheral nerve injuries in animal models, and (5) conclusions regarding outcome measures and studies needed to improve understanding of regeneration through ablated branched structures of the peripheral nervous system.